PELATIHAN IMPLEMENTASI PEMASARAN DIGITAL PRODUK PERTANIAN KWT RISKI DINARI DUSUN PAKIS KULON - Esperansa, Serafina Trixi; Lindya, Anggris Rahma Awal; Lestari, Feni Indah; Siva, Nur; Chaniago, Nur Sri Mulyaningsih; Ghifari, Muhammad Iqbal; Putra, Rizqi Fadhilah; Adha, Ikhsan Fauzi (Universitas Mataram, 2024)
Agricultural products are not always promising when through the relay sales system carried out by middlemen and low agricultural product prices. The use of digital marketing as a promotional medium makes it easier for sellers and buyers to make transactions, expand the reach of promotions, and help determine market needs effectively. Weak infrastructure and market information, small agricultural scale, lack of knowledge of business actors, and lack of good marketing policies are problems that cause inefficient marketing systems. Community service aims to enable women farmers who are members of KWT Riski Dinari to obtain effective digital marketing steps and strategies, introduction and development of applications that can be used for marketing in the digital world, so that the presence of applications can be an effective bridge in carrying out the digital marketing strategy of the KWT Riski Dinari organization. The method of implementing the activity was a workshop attended by mothers who are members of KWT Riski Dinari, the youth of Kulon hamlet, and the community. Activities carried out include material presentation, case examples, practice and evaluation. The result of the MBKM Mandiri Fikomm Community Service UMBY activity in 2024 is that participants slowly understand the use of social media. In addition, participants can learn how social media functions, trends that are currently on the rise, and learn how it impacts both personally and professionally. Thus, the implementation method provides a good understanding and skills to workshop participants in gaining knowledge related to how to use social media as a bridge in their business. Through the right platform, the understanding of digitalization workshops obtained by participants, active communities, and quality content produced will be a benchmark for successful acquisition and utilization related to digitalization.